IMPLEMENTASI KEBIJAKAN APBD DALAM MENINGKATKAN KINERJA KEUANGAN DAERAH DI KABUPATEN INDRAMAYU TAHUN 2020-2024: Implementation of Regional Budget (APBD) Policies in Improving Regional Financial Performance in Indramayu Regency During 2020–2024 - Sri Tresnaningsih; Rohadin Rohadin; Erna Erna (Jurnal Investasi, 2026)
This study analyzes the implementation of the Regional Revenue and Expenditure Budget (APBD) policy in improving the financial performance of the Indramayu Regency Government during 2020-2024. The analysis focuses on five regional financial ratios, namely independence, effectiveness, efficiency, activity, and growth ratios, as well as on the factors affecting regional financial management and the strategic plans formulated to improve future performance. The research applies a qualitative case study approach. Data were collected from APBD documents and budget realization reports for 2020-2024 and were enriched through interviews with officials of the Regional Finance and Asset Agency, the Regional Development Planning Agency, the Inspectorate, and members of the Regional House of Representatives. Data were analyzed through data reduction, categorization, interpretation of financial ratios, and triangulation between documentary and interview evidence. The findings show that APBD policy implementation has maintained very strong revenue effectiveness, with average revenue realization above 95 percent. The efficiency ratio ranges from 92 to 95 percent, indicating relatively efficient expenditure management. However, the independence ratio remains low because local own-source revenue contributes less than 20 percent of total regional revenue, leaving the regency highly dependent on transfers from central and provincial governments. The activity ratio reveals that operational spending still dominates, although the share of capital expenditure increased from 17.5 percent in 2020 to 20.2 percent in 2024. The growth ratio is positive, yet the pace of growth remains modest. Factors affecting regional financial management include limited own-source revenue, planning quality, inter-agency coordination, the dominance of operational expenditure, central government regulations, economic dynamics, and leadership commitment. The study concludes that improving Indramayu's financial performance requires optimization of local revenue, expenditure reorientation, stronger planning and internal control, and broader digitalization of regional financial management.